1975
DOI: 10.3382/ps.0540584
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Utilization of the Calcium Salt of Methionine Hydroxy Analogue by the Young Chick

Abstract: Six growth assays were conducted using crystalline amino acid diets to investigate the efficacy of methionine hydroxy analogue (OH-M) as a precursor of sulfur bearing amino acids (SAA). The influence on OH-M utilization of dietary modifications of the methionine-cystine ratio, inorganic sulfate as K2SO4 and supplemental mixtures of the branched-chain amino acids (leucine, isoleucine and valine) was explored. Performance of chicks fed OH-M was inferior to those fed an equivalent molar quantity of DL-methionine.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1977
1977
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…The lower toxicity of HMTBa compared with DL-Met has been also confirmed in Pekin ducks (Xie et al, 2007). There obviously exists an interaction between HMTBa and cyst(e)ine, as even small excesses of cyst(e)ine appear to depress feed intake and weight gain and reduce HMTBa utilisation compared with DL-Met (Katz and Baker, 1975;Baker and Boebel, 1980;Baker, 2007;Dilger and Baker 2008). …”
Section: Methionine and Its Analoguementioning
confidence: 60%
See 1 more Smart Citation
“…The lower toxicity of HMTBa compared with DL-Met has been also confirmed in Pekin ducks (Xie et al, 2007). There obviously exists an interaction between HMTBa and cyst(e)ine, as even small excesses of cyst(e)ine appear to depress feed intake and weight gain and reduce HMTBa utilisation compared with DL-Met (Katz and Baker, 1975;Baker and Boebel, 1980;Baker, 2007;Dilger and Baker 2008). …”
Section: Methionine and Its Analoguementioning
confidence: 60%
“…This may be attributable to differences in experimental design and response criteria, the incomplete conversion of HMTBa to L-Met (FerjancicBiagini et al, 1995) and species differences in HMTBa utilisation (see Baker, 2006). Moreover, Baker and co-workers have identified different dietary factors that may interfere with the utilisation of HMTBa; even small excesses of cyst(e)ine appear to reduce HMTBa utilisation, and differences in the utilisation of HMTBa and DL-Met (on a equimolar or isosulphurous basis) are more pronounced when crystalline amino acid diets are fed rather than diets containing intact protein (Katz and Baker 1975;Baker and Boebel, 1980;Christensen et al, 1980a, b;Baker, 2007, 2008).…”
Section: Comparative Bioefficacy Of the Methionine Enantiomers And Thmentioning
confidence: 99%
“…The latter group also found that MHA was less effective when fed with cystine than when fed with methionine. Scott et al (1966), Smith (1966), and Katz and Baker (1975) also have noted the increased efficacy of MHA when fed with a combination. The latter paper reports that one mixture of all three produced a gain as high as with the methionine-cystine combination, but feed efficiency was not as high.…”
Section: Resultsmentioning
confidence: 88%
“…Machlin and Gordon (1959), Harms et al (1976), Romoser et al (1976), and Bishop and Halloran (1977) found equal utilization of DL-methionine and MHA-Ca when added on an equimolar basis to chick diets. However, Tipton et al (1965Tipton et al ( , 1966, Smith (1966), Marret and Sunde (1965), Featherston and Horn (1974), Katz and Baker (1975), Boebel and Baker (1982), Schutte and Van Weerden (1981) and Van Weerden et al (1982) reported that MHA-Ca failed to support chick performance equivalent to DL-methionine.…”
Section: Introductionmentioning
confidence: 93%